1995
DOI: 10.1111/j.1365-2141.1995.tb08426.x
|View full text |Cite
|
Sign up to set email alerts
|

Desferrioxamine therapy accelerates clearance of iron deposits after bone marrow transplantation for thalassaemia

Abstract: We treated 18 heavily iron-loaded patients who had become ex-thalassaemics after bone marrow transplantation with subcutaneous desferrioxamine therapy for 5-20 months. As determined using serum ferritin concentration, transferrin saturation and stainable liver iron obtained in follow-up biopsies, marked decreases in body iron stores were observed with this regimen. Moreover, the liver Keywords desferrioxamine, BMT, iron overload, function tests demonstrate a trend to normalization in all

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 14 publications
(3 reference statements)
1
24
0
1
Order By: Relevance
“…Deferoxamine has been proved effective and safe with many experiences. [12][13][14] In our study, we found the correlation between the number of administration and the decrease of ferritin level. Also, the patients with increased ferritin level despite of the iron-chelating therapy received less deferoxamine.…”
Section: Discussionmentioning
confidence: 68%
“…Deferoxamine has been proved effective and safe with many experiences. [12][13][14] In our study, we found the correlation between the number of administration and the decrease of ferritin level. Also, the patients with increased ferritin level despite of the iron-chelating therapy received less deferoxamine.…”
Section: Discussionmentioning
confidence: 68%
“…Deferoxamine, approved by FDA for the removal of iron in conditions involving iron overload, such as β-thalassemia (Giardini et al 1993), has been used primarily as a metal chelating agent to block the iron-dependent hydroxyl radical (Goldstein and Czapski 1990). It may involve an additional or alternative antioxidant mechanism which would directly scavenge free radicals, such as superoxides (O 3 ) or nitrogen dioxide ( .…”
Section: Discussionmentioning
confidence: 99%
“…The iron burden slowly decreases after HCT, but the rate of decline is accelerated by regular phlebotomy or iron chelation therapy after HCT. [49][50][51] In Pesaro, a program utilizing regular phlebotomy has been successful in Classes 2 and 3 thalassemics after HCT. Reduction in the body iron burden was accompanied by lowering of the serum alanine aminotransaminase level and improvement in the histologic changes of chronic hepatitis C, observed in 85% of these patients.…”
Section: Complications After Hct B-thalassemiamentioning
confidence: 99%